2010
DOI: 10.1186/1471-2334-10-288
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein serum levels as an early predictor of outcome in patients with pandemic H1N1 influenza A virus infection

Abstract: BackgroundData for predicting which patients with pandemic influenza A (H1N1) infection are likely to run a complicated course are sparse. We retrospectively studied whether the admission serum C-reactive protein (CRP) levels can serve as a predictor of illness severity.MethodsIncluded were all consecutive adult patients who presented to the emergency department (ED) between May-December, 2009 with a flu-like illness, a confirmed diagnosis of pandemic influenza A (H1N1) infection and a serum CRP level measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
3
27
0
2
Order By: Relevance
“…Our results showed that H7N9-infected patients in critical conditions had higher C-reactive protein level and more severe renal insufficiency and myocardium injury. C-reactive protein level might be used as an early marker for clinical prognosis in H7N9 patients based on results from our logistic regression analyses, which was in agreement with previous studies showing that C-reactive protein level might serve as a marker for severity of illness in influenza infections [18,19]. Since multivariate analysis was not performed in our small sample study, further research is needed to verify this.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that H7N9-infected patients in critical conditions had higher C-reactive protein level and more severe renal insufficiency and myocardium injury. C-reactive protein level might be used as an early marker for clinical prognosis in H7N9 patients based on results from our logistic regression analyses, which was in agreement with previous studies showing that C-reactive protein level might serve as a marker for severity of illness in influenza infections [18,19]. Since multivariate analysis was not performed in our small sample study, further research is needed to verify this.…”
Section: Discussionsupporting
confidence: 91%
“…Serum levels of complement 3, prostaglandin E 2 , H 2 O 2 , and C-reactive protein (CRP) did not indicate a potential as a biomarker for influenza virus disease progression in BALB/c mice. These results are surprising as particularly CRP is a major acute-phase protein in humans and is used as an inflammatory marker of virus infections (Nakayama et al, 1993; Zimmerman et al, 2010) and other disease states (Kushner et al, 1978). Its usefulness in the mouse model is still debated though (Torzewski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…During seasonal epidemics from 3 to 5 million severe cases and about 250.000-500.000 lethal cases are registered worldwide [2]. Until now there has not been a laboratory test which has served as a potential marker for identification of patients with a high risk of developing severe clinical forms of influenza and lethal outcome [3,4]. It is known that patients with different comorbid conditions such as diabetes mellitus, chronic cardiovascular and pulmonary diseases, immunosuppressive conditions, adult patients and other conditions are at higher risk of developing severe clinical course of the disease and lethal outcome [5].…”
Section: Introductionmentioning
confidence: 99%